Beneficial metabolic actions of a stable GIP agonist following pre-treatment with a SGLT2 inhibitor in high fat fed diabetic mice. (15th January 2016) - Millar, P.J.B.; Pathak, V.; Moffett, R.C.; Pathak, N.M.; Bjourson, A.J.; O'Kane, M.J.; Flatt, P.R.; Gault, V.A.
Abstract: The purpose of the present study was to examine if a stable glucose-dependent insulinotropic polypeptide (GIP) agonist could exert beneficial metabolic control in diabetic mice which had been pre-treated with sodium-glucose-cotransporter-2 (SGLT2) inhibitor dapagliflozin (DAPA). High fat fed mice administered low dose streptozotocin (STZ) received vehicle, DAPA once-daily over 28 days, or DAPA once-daily for 14 days followed by (d Ala 2 )GIP once-daily for 14 days. Energy intake, body weight, glucose and insulin concentrations were measured at regular intervals. Glucose tolerance, insulin tolerance test, dual-energy X-ray absorptiometry (DEXA) and pancreatic histology were examined. Once-daily administration of (d Ala 2 )GIP for 14 days in high fat fed diabetic mice pre-treated with DAPA demonstrated significant decrease in body weight, blood glucose and increased insulin concentrations which were independent of changes in energy intake. Similarly, glucose tolerance, glucose-stimulated insulin secretion, insulin sensitivity and HOMA-β were significantly enhanced in (d Ala 2 )GIP-treated mice. DEXA analysis revealed sustained percentage body fat loss with no changes in lean mass, bone mineral content and density. Pancreatic immunohistochemical analysis revealed decreased islet number and increases in islet area, beta cell area and pancreatic insulin content. The DAPA-induced increase in alpha cell area was also reversed. Additional acute in vitro and in vivo experiments confirmed that the impaired action of (d Ala 2 )GIP under hyperglycaemic-induced conditions was significantly reversed by DAPA treatment. These data demonstrate that (d Ala 2 )GIP can exert beneficial metabolic control in high fat fed diabetic mice pre-treated with DAPA. The results highlight possibility of a targeted and personalized approach using a GIP agonist and SGLT2 inhibitor for the treatment of type 2 diabetes. Highlights: (d Ala 2 )GIP improved glucose tolerance, insulin secretion/sensitivity following DAPA pre-treatment. (d Ala 2 )GIP reversed DAPA-induced increase in alpha cell area. DAPA treatment reversed impaired action of (d Ala 2 )GIP under hyperglycaemic conditions. Possibility of therapy using a GIP agonist and SGLT2 inhibitor.